Optimalisasi Fungsi Pengawasan DPRD Terhadap Pembangunan Infrastruktur - Nugroho, Wahyu; Sudarmanto, Kukuh; Soegianto, Soegianto; Arifin, Zaenal (Universitas Semarang, 2024)
This research aims to analyze the use of the right of inquiry by the Regional People's Representative Council (DPRD) in Indonesia's state governance, particularly in overseeing infrastructure development in Sleman Regency. The urgency of this research lies in the need to strengthen the supervisory function of the Regional House of Representatives (DPRD) to ensure the effectiveness and transparency of regional development. The novelty of this research focuses on optimizing the role of the DPRD through a normative juridical approach and an in-depth analysis of the implementation of oversight functions involving the right of inquiry. This research uses a normative juridical method by examining legislation, literature, and empirical data related to the implementation of the DPRD's supervisory function. The research results show that the DPRD's oversight of infrastructure development in Sleman Regency has been effective, supported by adequate regulations, the commitment of DPRD members, as well as budgetary support, and the enhancement of human resource capacity through training. In addition, the harmonious relationship between the DPRD and the executive, as well as community participation, also strengthens the oversight. This research concludes that the optimization of the DPRD's supervisory function can be achieved through preventive and repressive oversight, both directly and indirectly, as well as across sectors. With effective oversight, it is hoped that development in Sleman Regency can proceed more transparently, accountably, and in accordance with the needs of the community without deviations that harm the state. Penelitian ini bertujuan untuk menganalisis penggunaan hak angket Dewan Perwakilan Rakyat Daerah (DPRD) dalam tata kelola negara Indonesia, khususnya dalam pengawasan pembangunan infrastruktur di Kabupaten Sleman. Urgensi penelitian ini terletak pada perlunya memperkuat fungsi pengawasan DPRD untuk memastikan efektivitas dan transparansi pembangunan daerah. Kebaruan penelitian ini terfokus pada optimalisasi peran DPRD melalui pendekatan yuridis normatif dan analisis mendalam terhadap implementasi fungsi pengawasan yang melibatkan hak angket. Penelitian ini menggunakan metode yuridis normatif dengan menelaah peraturan perundang-undangan, literatur, dan data empiris terkait pelaksanaan fungsi pengawasan DPRD. Hasil penelitian menunjukkan bahwa pengawasan DPRD terhadap pembangunan infrastruktur di Kabupaten Sleman telah berjalan baik, didukung oleh regulasi yang memadai, komitmen anggota DPRD, serta dukungan anggaran dan peningkatan kapasitas sumber daya manusia melalui pelatihan. Selain itu, hubungan harmonis antara DPRD dan eksekutif serta partisipasi masyarakat turut memperkuat pengawasan.Penelitian ini menyimpulkan bahwa optimalisasi fungsi pengawasan DPRD dapat dicapai melalui pengawasan preventif dan represif, baik secara langsung maupun tidak langsung, serta lintas sektor. Dengan pengawasan yang efektif, diharapkan pembangunan di Kabupaten Sleman dapat berjalan lebih transparan, akuntabel, dan sesuai dengan kebutuhan masyarakat tanpa penyimpangan yang merugikan negara.